Glycerophosphodiesterase GDE2 Promotes Neuroblastoma Differentiation through Glypican Release and Is a Marker of Clinical Outcome - Matas-Rico, Elisa; van Veen, Wouter H; Leyton-Puig, Daniela; van den Berg, Jeroen; Koster, Jan; Kedziora, Katarzyna M; Molenaar, Bas; J A Weerts, Marjolein; de Rink, Iris; Medema, René H; Giepmans, Ben N G; Perrakis, Anastassis; et al. (Elsevier, 2016)
Neuroblastoma is a pediatric embryonal malignancy characterized by impaired neuronal differentiation. A better understanding of neuroblastoma differentiation is essential for developing new therapeutic approaches. GDE2 (encoded by GDPD5) is a six-transmembrane-domain glycerophosphodiesterase that promotes embryonic neurogenesis. We find that high GDPD5 expression is strongly associated with favorable outcome in neuroblastoma. GDE2 induces differentiation of neuroblastoma cells, suppresses cell motility, and opposes RhoA-driven neurite retraction. GDE2 alters the Rac-RhoA activity balance and the expression of multiple differentiation-associated genes. Mechanistically, GDE2 acts by cleaving (in cis) and releasing glycosylphosphatidylinositol-anchored glypican-6, a putative co-receptor. A single point mutation in the ectodomain abolishes GDE2 function. Our results reveal GDE2 as a cell-autonomous inducer of neuroblastoma differentiation with prognostic significance and potential therapeutic value.
Keywords: Neuroblastoma; glycerophosphodiesterase; GDE2; G protein-coupled receptors; glypican; differentiation